A rapid review of evidence relating to service use, experiences, and support needs of adults from minority ethnic communities along the eyecare pathway in the United Kingdom - Heinze, Nikki; Jones, Lee; Makwana, Bhavini (Frontiers in Public Health, 2023)
Background: There is growing awareness of the health inequalities experienced by minority ethnic communities, who make up an increasing proportion of the United Kingdom (UK) population and have been found to be at increased risk of visual impairment (V.I.). V.I. impacts on a wide range of life domains including employment, social functioning and activities of daily living. Considering existing health inequalities, the increased risk of V.I. and its wide-ranging impact, it is important to understand the experiences of adults from minority ethnic communities living with V.I. in the UK. Methods: A rapid evidence review of academic and grey literature published since 2005 and in English was performed. A search of AMED, CINAHL Plus and MEDLINE via EBSCOhost identified 969 articles. Articles were included in the review if they reported findings relating to the UK-context, to adults from minority ethnic communities living with V.I., and to experiences of V.I. and the eyecare pathway. Results: A total of 11 academic articles and 4 charity reports presented findings relating to perceptions of V.I. and eye disease (n=3), access to services and service use (n=5), impact of interventions (n=7), the wider impact of V.I. (n=2), and registration status (n=1). Much of the literature focused on primary eyecare resulting in a comprehensive list of barriers and recommendations to increase eye tests. Less research addressed experiences and use of services further along the eyecare pathway although use of services may be low. Overall, the research on the experiences of adults with V.I. from minority ethnic communities in the UK remains anecdotal, outdated or unavailable. There are substantial gaps in the evidence relating to the wider impact of VI, the impact of perceptions of V.I., and the use of services beyond eye tests. Conclusions: This review summarises our current knowledge of the experiences of adults from minority ethnic communities living with V.I. in the UK and highlights substantial gaps in the evidence. The findings provide practical implications for practitioners and researchers committed to addressing health inequalities in the field of eyecare in the UK.